High-Performanced Hemicellulose Based Organic-Inorganic Films with Polyethyleneimine - Han Wu (MDPI AG, 2021)
For the high-value utilization of hemicellulose-based composite films, the poor film-forming and mechanical properties of hemicellulose-based composite films must be surmounted crucially. Based on this, hemicellulose-based organic-inorganic composite films with good mechanical properties were prepared from quaternized hemicelluloses (QH), bentonite, and polyethyleneimine (PEI). The QH/PEI/bentonite composite films were prepared by vacuum filtration, and the properties of the composite film were investigated. The results showed that the QH was inserted into bentonite nanosheets through hydrogen bonding and electrostatic interactions. PEI was cross-linked with hemicellulose by hydroxyl groups, electrostatically attracted by the bentonite flake layers. The mechanical properties of the composite films were significantly increased by the incorporation of PEI. When the PEI content was 20%, the tensile stress of the composite film was increased by 155.18%, and the maximum tensile stress was reached 80.52 MPa. The composite films had strong UV absorption ability with the transmittance was almost 0 in the UV region from 200 to 300 nm. The thermal property of composite film was also improved, and the residual mass increased by three times compared to QH. These results provide a theoretical basis for the use of hemicellulose-based composite films in packaging applications.